Microsecond-long simulation reveals the molecular mechanism for the dual inhibition of falcipain-2 and falcipain-3 by antimalarial lead compounds - Danazumi, Ammar Usman; Balogun, Emmanuel Oluwadare (Frontiers in Molecular Biosciences, 2022)
The latest world malaria report revealed that human deaths caused by malaria are currently on the rise and presently stood at over 627,000 per year. In addition, more than 240 million people have the infection at any given time. These figures make malaria the topmost infectious disease and reiterate the need for continuous efforts for the development of novel chemotherapies. Malaria is an infectious disease caused majorly by the protozoan intracellular parasite Plasmodium falciparum and transmitted by mosquitoes. Reports abound on the central role of falcipains (cysteine protease enzymes) in the catabolism of hemoglobin for furnishing the plasmodium cells with amino acids that they require for development and survival in the hosts. Even though falcipains (FPs) have been validated as drug target molecules for the development of new antimalarial drugs, none of its inhibitory compounds have advanced beyond the early discovery stage. Therefore, there are renewed efforts to expand the collection of falcipain inhibitors. As a result, an interesting finding reported the discovery of a quinolinyl oxamide derivative (QOD) and an indole carboxamide derivative (ICD), with each compound demonstrating good potencies against the two essential FP subtypes 2 (FP-2) and 3 (FP-3). In this study, we utilized microsecond-scale molecular dynamics simulation computational method to investigate the interactions between FP-2 and FP-3 with the QOD and ICD. The results revealed that QOD and ICD bound tightly at the active site of both enzymes. Interestingly, despite belonging to different chemical scaffolds, they are coordinated by almost identical amino acid residues via extensive hydrogen bond interactions in both FP-2 and FP-3. Our report provided molecular insights into the interactions between FP-2 and FP-3 with QOD and ICD, which we hope will pave the way towards the design of more potent and druglike inhibitors of these enzymes and will pave the way for their development to new antimalarial drugs.